Sleep Quality and Quantity in Low-Income Postpartum Women. Issue 3 (May 2017) - Doering, Jennifer J.; Szabo, Aniko; Goyal, Deepika; Babler, Elizabeth
Abstract: Purpose: To describe and explore patterns of postpartum sleep, fatigue, and depressive symptoms in low-income urban women. Study Design and Methods: In this descriptive, exploratory, nonexperimental study, participants were recruited from an inpatient postpartum unit. Subjective measures were completed by 132 participants across five time points. Objective sleep/wake patterns were measured by 72-hour wrist actigraphy at 4 and 8 weeks. Mean sample age was 25 years, high school educated with 3.1 children. Over half the sample reported an annual income less than 50% of the federal poverty level. Results: Objectively, total nighttime sleep was 5.5 hours (week 4) and 5.4 hours (week 8). Subjectively, 85% met criteria for "poor sleep quality" at week 4, and nearly half were persistently and severely fatigued through 8 weeks postpartum. Clinical Implications: The majority (65%) of women in this study met the definition of "short sleep duration, " defined as sleeping ⩽ 6 hours per night. Adverse effects of this short sleep on physical and mental health as well as safety and functioning, especially within the context of poverty, may be profound. There is an urgent need for further research on sleep in low-income underrepresented women to identify interventions that can improve sleep and fatigue as well as discern the implications of sleep deprivation on the safety and physical and mental health of this population. Abstract : Patterns of postpartum sleep, fatigue, and depressive symptoms were studied in low income urban women. Findings suggest adverse effects of inadequate sleep on physical and mental health as well as safety and functioning, especially within the context of poverty, may be profound.